2020
DOI: 10.1111/jce.14366
|View full text |Cite
|
Sign up to set email alerts
|

Electrogram‐only guided approach to His bundle pacing with minimal fluoroscopy: A single‐center experience

Abstract: Introduction His bundle pacing (HBP) is the most physiological pacing. The standard technique based on fluoroscopic approach might be challenging and fluoro consuming. Targeting the His guided exclusively by the electrical signals could enable a precise lead implant, thus reducing fluoroscopy time (FT) and X‐ray dose, desirable both for patients and operators. The aim of the study is to evaluate the feasibility, efficacy, and safety both acutely and at 30 days of the electrogram (EGM)‐guided HBP with minimal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 28 publications
(43 reference statements)
0
15
0
Order By: Relevance
“…[ 55 , 56 ] Alternately, an EGM-only guided approach to successful HBP with minimal fluoroscopy was recently reported by Zanon et al to be compatible with use of the SelectSecure 3830 lead. [ 57 ] Automated analysis of HBP ECGs is in development and this has the potential to facilitate even more rapid uptake of the technique. [ 24 ] Meanwhile, new evidence is gathering regarding the relative efficacy of LBBP compared with HBP, and its ECG characteristics are being more rigorously codified.…”
Section: Recent Advances and Future Directions In Conduction System Pmentioning
confidence: 99%
“…[ 55 , 56 ] Alternately, an EGM-only guided approach to successful HBP with minimal fluoroscopy was recently reported by Zanon et al to be compatible with use of the SelectSecure 3830 lead. [ 57 ] Automated analysis of HBP ECGs is in development and this has the potential to facilitate even more rapid uptake of the technique. [ 24 ] Meanwhile, new evidence is gathering regarding the relative efficacy of LBBP compared with HBP, and its ECG characteristics are being more rigorously codified.…”
Section: Recent Advances and Future Directions In Conduction System Pmentioning
confidence: 99%
“…Zanon et al demonstrated that HBP can be performed primarily using an electrogram with zero or minimal fluoroscopy with high success rates. [ 12 ] In that study, the sheath, along with the lead, was advanced gently with counterclockwise and clockwise rotation into the right atrium through a standard 7 Fr introducer. The pacing lead was then connected to the alligator cable in a unipolar fashion.…”
Section: His Bundle Pacing: Implantation Techniquementioning
confidence: 99%
“…Further anticlockwise rotation helped reach the HB area. [ 12 ] Gentle manipulation of the system helped record a clear near-field His potential from the pacing lead. Unipolar threshold measurement was performed at a pulse width of 1 ms before fixing the lead in the membranous septum.…”
Section: His Bundle Pacing: Implantation Techniquementioning
confidence: 99%
“…We appreciate the letter from Serkan Cay 1 and colleagues entitled "Simple Approaches to Reduce Radiation in the Electrophysiology Laboratory." 2 We agree with Serkan and colleagues that fluoroscopy time per se is not enough and that dose area product, air kerma, frame rate, and various autoregulated variables are more important data. We completely agree with the observation regarding the physics of the dose radiation and are very grateful to our colleagues for their accurate explanation and involvement in the field.…”
Section: Simple Approaches To Reduce Radiation In the Electrophysiolomentioning
confidence: 99%